Proceedings of the Bipolar/BiCMOS Circuits and Technology Meeting, 2005.
DOI: 10.1109/bipol.2005.1555204
|View full text |Cite
|
Sign up to set email alerts
|

New lateral DMOS and IGBT structures realized on a partial SOI substrate based on LEGO process

Abstract: In this paper, we present new lateral DMOS and IGBT structures based on a partial SOI substrate. The partial SOI substrate, formed through LEGO recrystallization process improves considerably the breakdown capability and the thermal behavior of these devices compared to full SOI devices. Experimental results of high voltage power devices implemented on such a process are presented for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Over the defective area, a slight decrease in the breakdown voltage on ECS Transactions, 6 (4) 327-332 (2007) some of the diodes could be observed but the related leakage current stays within the range of the reference one. Finally, in a previous work (3), it was also demonstrated that the device quality of the SOI layers allowed successfully implementing high voltage LIGBT and LDMOS devices. They exhibited a measured breakdown voltage of 300V as expected from simulations.…”
Section: Electrical Resultsmentioning
confidence: 91%
“…Over the defective area, a slight decrease in the breakdown voltage on ECS Transactions, 6 (4) 327-332 (2007) some of the diodes could be observed but the related leakage current stays within the range of the reference one. Finally, in a previous work (3), it was also demonstrated that the device quality of the SOI layers allowed successfully implementing high voltage LIGBT and LDMOS devices. They exhibited a measured breakdown voltage of 300V as expected from simulations.…”
Section: Electrical Resultsmentioning
confidence: 91%
“…The lowly doped substrate which was electrically connected to the source allowed the depletion region to spread into it and supported part of the voltage, releasing the pressure on the insulating and thin SOI layers. Further development of the LIGBT on PSOI was reported later in 2005 [84] which successfully realized the LIGBT structure based on lateral epitaxial growth over oxide (LEGO) process [85]. The resulted device showed a turn-off time of 400ns, BV more than 300V with reduced heating effect when compared to a standard SOI.…”
Section: Partial Isolation Soi (Psoi) Ligbtmentioning
confidence: 95%
“…Lateral Insulated Gate Bipolar Transistors (LIGBTs) and Superjunction (SJ) devices in PSOI were initially proposed in [7,8,9]. Over the years the topic was investigated by several academic teams and their achievements include the LEGO (Lateral Epitaxial Growth over Oxide) process [10].…”
Section: A History and Commercial Implementationsmentioning
confidence: 99%